Stan Smith's Guide to Better Tennis - Smith, Stan, 1946-; Edited by Sheehan, Larry (New York Grosset and Dunlap, 1975)
Using a system of defining a "fault" and then prescribing a "cure," this guide illustrates techniques for improving the tennis game.
Include Color Illustration
Keywords: Tennis